Allocation of expenditures in elderly households and the cost of widowhood - Daniel Burkhard (University of Bern, Department of Economics, 2015)
Widowhood and retirement are likely to change the economic environment of elderly households. While retirement primarily changes income and expenditure patterns, widowhood fundamentally changes the structure of the household. Beside high non-monetary cost of losing the partner, resources are no longer shared and economies of scale arising from joint consumption are lost. This paper applies the Lewbel and Pendakur (2008) collective household model to expenditure data on elderly households in Switzerland. The findings suggest that between 40 and 50% of household resources are assigned to wives and both spouses save approximately 25% on expenditures due to economies of scale in consumption. Widowers tend to have higher wealth than widows. Estimates of indifference scales, however, indicate that the financial loss related to widowhood is larger for men than for women. Moreover, ignoring within household inequality, as implicitly done by traditional equivalence scales, underestimates total inequality among individuals.
Keywords: D12; D13; C30; 330; Collective Household Model; Indifference Scale; Resource Shares; Economies of Scale in Consumption; Demand System Estimation; Engel Curves; Elderly Households